Evaluation of the effects of copper electroplating parameters on the adhesion using response surface methodology - Mohamed Haider, Farag I., Suryanto; Ani, Mohd Hanafi; Mahmood, Mahmood Hameed (Trans Tech Publications, 2017)
In this paper, response surface methodology (RSM) was utilized for the experiment design of CuSO4 and H2SO4 concentrations and current densities. RSM was also used to evaluate the significance of each parameter and its interaction on the adhesion strength of austenitic stainless steel substrate. Adhesion strength was investigated by a Teer ST-30 tester, and the structure of the samples investigated by using scanning electron microscopy (SEM). Results showed that increasing the concentration of CuSO4 and decreasing that of H2SO4 strengthens adhesion. Conversely, the current density only has a slight effect.